Hypericum alacamdaglariense (Hypericaceae), a new species from Turkey - Duman Hayri̇; Çakir-Di̇ndar Ece Gökçe (Phytotaxa, 2020)
The new species Hypericum alacamdaglariense, which belongs to the section Triadenioides, is described and illustrated. Its habitat and ecology, distribution map and conservation status are also provided. The new species is also compared to the closely related H. pallens and H. vacciniifolium in terms of their morphological features.